Evaluation of the Jurisprudential Principles of Civil Responsibility - Hussein Hooshmand Firoozabadi (آموزه‌‌های فقه مدني, 2019)
The two jurisprudential principles that proposed as the basis of civil responsibility are: customary invoking of the harm to the damaging and respecting of victim. The question is, which of these jurisprudential foundations can justify the liability which is a positive rule and the basis of civil liability? By not accepting the opinion of those who considered the liability of the kinsman as a positive rule and considered it to be annulling of the theory of the customary invoking, this article has emphasized on imperative rule of the liability of the kinsman. The reason for not accepting the theory of customary invoking as the basis is the lack of providing a positive criterion and standard and confusion between the basis of civil responsibility and one of its pillars (causality relation). In the following, by examining the traditional arguments of the respect, the extraction of the positive rule of liability from the verses such as “the unlawful ownership” and the narratives such as “the relevance of the believer’s property is the same as his blood” is a perfect argument. By proving the domain of the theory of respect for physical, financial and spiritual damage to Muslims and non-Muslims, “respect” has been accepted as a jurisprudential basis for civil responsibility.